Does survival context enhance memory for source? A within-subjects comparison. Issue 6 (3rd July 2019) - Misirlisoy, Mine; Tanyas, Hilal; Atalay, Nart Bedin
ABSTRACT: Nairne, Thompson, and Pandeirada [2007. Adaptive memory: Survival processing enhances retention. Journal of Experimental Psychology: Learning, Memory, and Cognition, 33, 263–273] demonstrated that processing words according to their relevance to a survival scenario enhanced their subsequent retrieval in recall and recognition tasks compared to a variety of control scenarios. From an adaptive perspective, it is maintained that processing words in a survival context should also enhance memory for source; however, evidence in the literature is rather mixed regarding a survival context advantage for source memory. In the current study, we conducted four experiments to systematically investigate the survival advantage in source memory, when the context itself is the source, with both recall (Experiments 1A and 1B) and recognition tests (Experiments 2A and 2B). Results showed a survival advantage for item memory over the control contexts in all experiments. The survival context advantage was not extended to source memory performance in Experiment 1A. Results from all other experiments, however, indicated a survival context advantage for both item and source memory. Findings are discussed in relation to possible proximate mechanisms underlying the survival processing effect.